Pengembangan Media Pembelajaran Melalui Software Lectora Inspire Materi Wujud Zat Dan Perubahannya Berbasis Model Pembelajaran Problem Based Learning - Desih, Desih; Taufik, M; Setiawan, Sigit (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
The use of technology-based learning media is able to raise students' learning motivation, especially in science and science learning. The aim of this research is to find out the development process, feasibility and response of students to the Lectora Inspire media, material on the form of substances and its changes based on the problem based learning model in class IV of Sindangmandi State Elementary School. The research and development (R&D) method used is the ADDIE model which consists of five stages, namely Analyze, Design, Development, Implementation and Evaluation. The research was conducted on 22 students in class IV of Sindangmandi State Elementary School. Based on the research results, Lectora Inspire media is very suitable for use in learning activities. This is proven by the validation results carried out by experts. Validation from two media experts with a percentage of 89.5% is in the "Very Eligible" category. The validation score from two material experts with a percentage of 83.125% is in the "Very Eligible" category. Then validation from two language experts with a percentage of 91.25% which is in the "Very Eligible" category. So the overall validation results from all experts with a percentage of 87.95% were in the "Very Decent" category and student responses with a percentage of 98.4% were in the "Very Good" category.